Language development in children with congenital heart disease aged 12–24 months. (May 2019) - Fourdain, Solène; St-Denis, Ariane; Harvey, Julien; Birca, Ala; Carmant, Lionel; Gallagher, Anne; Trudeau, Natacha; ,
Abstract: This longitudinal study aims to describe the trajectory of language development in children with CHD aged 12–24 months assessed through an early monitoring and individualized intervention program. We also sought to determine whether early language performances, at 12 months of age, predict 24-month language abilities. We conducted developmental assessments of 49 children with CHD using the Bayley Scales of Infant and Toddler Developmental, third edition (Bayley-III) at 12 and 24 months, and the MacArthur-Bates Communicative Development Inventories (MBCDI) at 12, 18 and 24 months. Compared to normative populations, CHD patients showed significantly lower mean scores in both receptive and expressive language scales of the Bayley-III and the MBCDI at 12 months, whereas at 18 and 24 months only expressive language scores were reduced. No differences were found in the cognitive scale. Communicative gestures at 12 months were significantly predictive of language skills at 24 months of age. Our findings indicate specific vulnerability of language outcome, especially in expressive skills, rather than a global cognitive impairment in our patients with CHD. We recommend using communicative gestures as an early marker of language development to improve our ability to detect language delays in this population. Highlights: It is the first longitudinal study to investigate early language trajectory in children with CHD. Our patient group exhibit specific language impairments, but normal intellectual functioning. Expressive skills remain impaired compared to norms up to 24 months, while receptive skills tend to recover. 12-month communicative gestures are a marker of future language abilities. Communicative gestures should be used to detect language delays.